2021
DOI: 10.3390/life11060581
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalphalipoproteinemia and Beyond: The Role of HDL in Cardiovascular Diseases

Abstract: Hyperalphalipoproteinemia (HALP) is a lipid disorder characterized by elevated plasma high-density lipoprotein cholesterol (HDL-C) levels above the 90th percentile of the distribution of HDL-C values in the general population. Secondary non-genetic factors such as drugs, pregnancy, alcohol intake, and liver diseases might induce HDL increases. Primary forms of HALP are caused by mutations in the genes coding for cholesteryl ester transfer protein (CETP), hepatic lipase (HL), apolipoprotein C-III (apo C-III), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 168 publications
(211 reference statements)
2
15
0
10
Order By: Relevance
“…Although HDL is known primarily as a factor that protects the cardiovascular system from damage caused by cholesterol deposition in blood vessel walls and tissues and has anti-inflammatory effects, studies have shown that elevated HDL levels may in turn be pro-inflammatory and pro-atherogenic [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although HDL is known primarily as a factor that protects the cardiovascular system from damage caused by cholesterol deposition in blood vessel walls and tissues and has anti-inflammatory effects, studies have shown that elevated HDL levels may in turn be pro-inflammatory and pro-atherogenic [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em suma, a HALP sendo um distúrbio promovido pelos elevados níveis de colesterol de HDL, ou seja, acima do percentil 90 para uma população geral (Laurinavicius, et al, 2016), é marcada por diversas mutações, como já abordado anteriormente, nos genes que codificam a CETP, lipase hepática (LIPC) e apolipoproteína C III (Giammanco, et al, 2021).…”
Section: Membranaunclassified
“…Quanto ao processo de formação da membrana dessas partículas de lipoproteínas, elas sucedem de copiosos regimes de remodelação e de transformação interpostos por enzimas de ordem plasmática e de fatores de transcrição, que são característicos, como já se sabe, do dogma central da biologia molecular (Giammanco, et al, 2021).…”
Section: Membranaunclassified
See 2 more Smart Citations